Onset of autotomy in an attached Cycloseris coral - Bert W Hoeksema; Zarinah Waheed (2012)
(Scleractinia: Fungiidae) are either complete individuals or fragments in various stages of fission and regeneration (Hoeksema and Waheed 2011). Their fragmentation is initiated by a process of radial skeleton dissolution called autotomy (Yamashiro et al. 1989; Yamashiro and Nishihira 1994). Only unattached fragmenting corals are known, representing the adult anthocyathus stage. The anthocaulus stage in which juveniles of free-living species are still attached, as in